Self-recovering near-infrared stress luminescent alumina-based smart material and preparation method thereof
By using alumina as a matrix and high-temperature solid phase method to prepare and dopant elements such as Cr, the limitations of the performance and cost of existing high-brightness near-infrared stress luminescent materials are solved, and low-cost, high-brightness and good stability are achieved. Near infrared stress luminescent material.
Patent Information
- Application Number
- CN202410006686.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-01-03
Smart Images

Figure CN118064139B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic luminescent materials, and in particular relates to a self-recovering near-infrared stress luminescent alumina-based intelligent material and a preparation method thereof. Background Art
[0002] At present, the commonly used existing technologies in the industry are as follows:
[0003] Mechanoluminescence (ML) material is an emerging optoelectronic functional material that produces luminescence when subjected to mechanical stress. Stress luminescence (mechanical force excitation) is a novel luminescence method. Different from the common photoluminescence (light excitation) and electroluminescence (electrical excitation), it directly produces luminescence when the material is subjected to external stress without the need for power or light exposure. According to the size of the stress and the elastic threshold of the stressed material, mechanoluminescence materials can be roughly divided into fracture mechanoluminescence materials, plastic mechanoluminescence materials and elastic mechanoluminescence materials. In addition, according to the material properties, it can be divided into self-recovery type and trap-controlled type that requires pre-excitation.
[0004] Inorganic luminescent materials are one of the important luminescent materials with stable structure and excellent performance. As a new type of inorganic luminescent body, the research of stress luminescent smart materials is a hot research field, which can play a huge potential application in the fields of artificial intelligence, new light sources, stress sensing, touch screen technology and electronic skin. In recent years, with the continuous research and discovery of high-brightness stress luminescent materials, new application fields have been opened up. The light waves with high emission energy can be used as the excitation light source for display and lighting, realizing the adjustable light and the emission of white light; therefore, stress luminescence also shows attractive practical prospects in the fields of multi-color display and white light lighting.
[0005] However, there is still a lack of high-brightness near-infrared stress luminescent materials. The traditional near-infrared stress luminescent materials reported so far include CaZnOS:Nd 3+ (ML peak 908nm, 1094nm, 1390nm): ACSapplied materials&interfaces, 2018, 10(17): 14509-14516, Sr3Sn2O7:Nd 3+ (ML peak 900nm): Journal of the American Ceramic Society, 2019, 102(10): 5899-5909, LiNbO3:Nd 3+(ML peak 895nm, 928nm, 938nm): Journal of Materials Chemistry C, 2019, 7(21): 6301-6307, LiGa5O8:Pr 3+ (ML peak 861nm, 913nm): Advanced Optical Materials, 2019, 7(24): 1901107, etc.; SrZnSO:Nd reported by Xiamen University 3+ / Tm 3+ / Er 3+ / Yb 3+ (ML peak 908nm, 1094nm, 1390nm / 790nm / 1534nm / 980nm), SrZn2S2O:Yb 3+ (ML peak 980nm), SrSi2O2N2:Yb 3+ (ML peak 980nm): Nano Energy, 2020, 68: 104329, etc. Chromium-doped near-infrared stress luminescence includes LiGa5O8:Cr reported by Beijing University of Science and Technology 3+ (ML peak 716nm), ZnGa2O4:Cr 3+ (ML peak 700nm), Zn3Ga2GeO8:Cr 3+ (ML peak 700nm), SrGa 12 O19:Cr 3+ (ML peak 750nm): Advanced Functional Materials, 2021, 31(19): 2010685; Y3Al5O reported by Kunming University of Science and Technology 12 :Cr 3+ (ML peak 688nm): Advanced Functional Materials, 2023, 33(27): 2214497; LaAlO3:Cr reported by South China University of Technology 3+ :Advanced PowderMaterials,2024,3(2):100165; SrAl2O4:Eu-Cr system developed by Japan Advanced Industrial Technology Research Institute:Journal of The Electrochemical Society,2021,168(4):047508; ECS Transactions,2020,98(11):61; CN 105209572A, etc.
[0006] The difference between the near-infrared stress luminescent material of the above invention and the material of this patent is:
[0007] First, the wavelength is different. The luminescent wavelength of the present invention is in the 600nm-900nm band, and the main wavelength is in the red light band (ML wavelength peak is 694nm); second, compared with other materials, aluminum oxide has lower cost, which gives it obvious advantages in large-scale preparation and application; third, aluminum oxide exhibits stable physical properties (wear resistance, corrosion resistance, biocompatibility and high-temperature stability), has relatively loose requirements on environmental conditions and excitation light sources, and has a wider range of application scenarios. It can be used as ceramic materials, electronic materials, biomedical materials, grinding materials, thermal barrier coating materials, etc. Different from the previously reported aluminum oxide photoluminescence and ultrahigh pressure fracture mechanical luminescence: Physical Review B, 2002, 66(1): 014108 (12-45 GPa ultrahigh pressure); Journal of luminescence, 2014, 154: 511-514 (fracture luminescence), the doped aluminum oxide in the present invention is a self-recovering near-infrared stress luminescence that can be directly observed under moderate mechanical force / pressure (~10 kPa) without the need for light source excitation and has highly repeatable luminescence (>100 times).
[0008] In summary, the problems existing in the prior art are:
[0009] The matrix structure of many traditional materials such as sulfide materials and doped fluorescent materials is relatively complex, including factors such as lattice structure, defect type, and grain size. This complexity makes the performance control and optimization of materials very challenging. At the same time, different matrix structures may lead to differences in material properties, which is unfavorable for some specific applications. Previous near-infrared stress luminescent materials, such as CaZnOS, Sr3Sn2O7, LiNbO3, LiGa5O8, ZnGa2O4, SrZn2S2O, Y3Al5O 12 The crystal structure composed of multi-element ions such as SrAl2O4 is complex in structure, and most of them need to use full rare earth doping to have stress. Stress luminescence comes from the ff forbidden transition of rare earth ions, and the luminescence efficiency is low. And single metal element ion compounds, such as Ga2O3, are expensive, which limits their competitiveness in large-scale applications. The price of Ga2O3 Aladdin is 899.9 yuan per 100g (about 9.0 yuan / g), while the price of the matrix Al2O3 Aladdin in the present invention is 113.9 yuan per 100g (about 1.1 yuan / g), which is nearly 8 times different. And Ga2O3 is currently a national strategic new material, and export restrictions are imposed. These characteristics make traditional near-infrared stress luminescent materials have certain limitations in terms of performance and cost. In addition, SrAl2O4:Eu-Cr system has a complex structure, and the preparation of this material needs to be carried out in a reducing atmosphere, and organic acid is required to assist in the generation of products. This preparation process is complicated and costly. Summary of the invention
[0010] In view of the problems existing in the prior art, the present invention provides a self-recovering alumina-based near-infrared stress luminescent material and a preparation method thereof.
[0011] The present invention is a self-recovering near-infrared stress luminescent alumina-based smart material, which is low-priced, has a luminescent wavelength in the 600nm to 900nm band, and a dominant wavelength in the near-infrared band (NIR-I). The material will directly emit light under stress without prior illumination. The purpose of this invention is to provide a near-infrared stress luminescent material and a preparation method thereof to solve the current problem of the shortage of near-infrared stress luminescent materials.
[0012] The material has high-intensity elastic stress luminescence properties, simple preparation process, low cost, and stable chemical properties. It can directly respond to different forms of mechanical force signals, such as compression, stretching, bending, collision, friction, torsion, etc., and the emitted light can be observed by the naked eye in a dark environment.
[0013] The chemical formula of the self-recovering near-infrared stress luminescent alumina-based smart material of the present invention is Al2O3: m%Cr-n%Rz%D; 0.000001≤m≤10.9; 0≤n≤15; 0≤z≤120; R is selected from one or more of Ti, Zr, Fe, Mn, Cu, Co, Ni, Bi, Sb, Sn, Ag, P, Ta, W, Y, La, D is added as a co-solvent, and D is selected from one or more of Li, Na and K; m, n, z represent molar percentages; the stress luminescent material is prepared by a high-temperature solid phase method. The preparation process includes the following steps:
[0014] a) Raw materials: Cr2O3 is used as the raw material for Cr and Al2O3 is used as the raw material for the matrix. First, weigh the raw materials of each element according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate mortar until they are evenly mixed. Then, place the mixed powder at 40~
[0015] After drying in an oven at 300°C, the desired pink stress-luminescent material is finally obtained;
[0016] b) placing the evenly ground powder in an alumina crucible, heating it to 1300-1650° C. at a heating rate of 1-100° C. / min in air, burning it for 0.5-24 hours, and finally cooling it naturally with the furnace;
[0017] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress-luminescent Al2O3:Cr powder.
[0018] The prepared self-recovering near-infrared stress luminescent material is ground and sieved into powder to form a composite with the optically transparent organic polymer elastic material PET and made into a thin sheet or coated on the surface of the component to be tested. Under the action of external mechanical force, the stress of the composite or the component can be converted into light emission, realizing high-brightness near-infrared force-light direct energy conversion.
[0019] The near-infrared stress luminescent material of the present invention is characterized in that the stress luminescent peak is a narrow spectrum peak located near 694nm, and the luminescent wavelength is in the range of 600nm to 900nm. The material can be directly observed by naked eyes in the dark or under natural light conditions.
[0020] The near-infrared stress luminescent material of the present invention is characterized in that, within the elastic limit, the elastic stress luminescent intensity of the material is proportional to the magnitude of the applied mechanical force.
[0021] The following are the beneficial effects of the present invention:
[0022] 1) The material of the present invention is prepared by a traditional high-temperature solid phase method, and the material preparation method is simple, easy to prepare, and has no rare earth and low cost.
[0023] 2) The material of the present invention has near-infrared red stress luminescence characteristics, which can be directly observed under dark conditions when a certain mechanical force is applied to the material.
[0024] 3) The materials of the present invention can be widely used in many fields such as force sensing, bio-imaging, anti-counterfeiting, military, etc. This type of material provides a potential solution to the current energy crisis and also broadens new horizons for multi-path energy conversion. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a flow chart of the near-infrared stress luminescent material in the present invention.
[0026] Figure 2 This is the stress luminescence spectrum of Al2O3:Cr, the product of Example 1 of the present invention.
[0027] Figure 3 It is a repeated data spectrum of the stress luminescence integrated intensity of Al2O3:Cr, the product of Example 1 of the present invention.
[0028] Figure 4 It is the stress luminescence integrated intensity diagram of Al2O3:Cr products of Examples 1 to 8 (different temperatures) of the present invention.
[0029] Figure 5 It is the stress luminescence spectrum of Al2O3:Cr of the products (different concentrations) of Examples 9 to 14 of the present invention.
[0030] Figure 6It is the XRD spectrum of Al2O3:Cr products of Examples 1 to 8 (different temperatures) of the present invention. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific examples. However, it should be understood that these examples are only used to illustrate the present invention and do not constitute a limitation on the scope of the present invention.
[0032] like Figure 1 As shown, the method for preparing the near-infrared stress luminescent material provided in Example 1 of the present invention comprises the following steps:
[0033] Step 1: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0034] Step 2: Place the evenly ground powder in an alumina crucible, compact it and cover it with a lid, heat it to 1650°C in air at a heating rate of 1-100°C / min, burn it for 4 hours, and finally cool it down naturally with the furnace;
[0035] Step 3: Crush and grind the cooled powder, and pass it through a 150-mesh sieve to obtain near-infrared stress luminescent powder Al2O3:0.5%Cr.
[0036] [Example 1]
[0037] Taking Al2O3:0.5%Cr at 1650℃ as an example, the specific operation steps are as follows:
[0038] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0039] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, burning for 4 hours, and finally cooling it naturally with the furnace;
[0040] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr powder.
[0041] [Example 2]
[0042] Taking 1600℃Al2O3:0.5%Cr as an example, the specific operation steps are as follows:
[0043] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0044] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, and finally cooling it naturally along with the furnace;
[0045] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr powder.
[0046] [Example 3]
[0047] Taking 1550℃ Al2O3:0.5%Cr as an example, the specific operation steps are as follows:
[0048] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0049] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1550°C at a heating rate of 5°C / min, and finally cooling it naturally along with the furnace;
[0050] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr powder.
[0051] [Example 4]
[0052] Taking 1500℃Al2O3:0.5%Cr as an example, the specific operation steps are as follows:
[0053] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0054] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1500°C at a heating rate of 5°C / min, and finally cooling it naturally along with the furnace;
[0055] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr powder.
[0056] [Example 5]
[0057] Taking 1450℃ Al2O3:0.5%Cr as an example, the specific operation steps are as follows:
[0058] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0059] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1450°C at a heating rate of 5°C / min, and finally cooling it naturally with the furnace;
[0060] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr powder.
[0061] [Example 6]
[0062] Taking 1400℃Al2O3:0.5%Cr as an example, the specific operation steps are as follows:
[0063] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0064] b) placing the evenly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1400°C at a heating rate of 5°C / min, burning it for 4 hours, and finally cooling it naturally with the furnace;
[0065] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr powder.
[0066] [Example 7]
[0067] Taking 1350℃ Al2O3:0.5%Cr as an example, the specific operation steps are as follows:
[0068] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0069] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1350°C at a heating rate of 5°C / min, keeping it at that temperature for 4 hours, and finally cooling it naturally with the furnace;
[0070] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr powder.
[0071] [Example 8]
[0072] Taking 1300℃ Al2O3:0.5%Cr as an example, the specific operation steps are as follows:
[0073] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0074] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1300°C at a heating rate of 5°C / min, keeping it at that temperature for 4 hours, and finally cooling it naturally with the furnace;
[0075] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr powder.
[0076] [Example 9]
[0077] Taking Al2O3:10%Cr at 1650℃ as an example, the specific operation steps are as follows:
[0078] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0079] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, keeping the temperature for 4 hours, and finally cooling it naturally with the furnace;
[0080] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:10%Cr powder.
[0081] [Example 10]
[0082] Taking Al2O3:4%Cr at 1650℃ as an example, the specific operation steps are as follows:
[0083] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0084] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, keeping the temperature for 4 hours, and finally cooling it naturally with the furnace;
[0085] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:10%Cr powder.
[0086] [Example 11]
[0087] Taking Al2O3:2%Cr at 1650℃ as an example, the specific operation steps are as follows:
[0088] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0089] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, keeping the temperature for 4 hours, and finally cooling it naturally with the furnace;
[0090] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:10%Cr powder.
[0091] [Example 12]
[0092] Taking Al2O3:1%Cr at 1650℃ as an example, the specific operation steps are as follows:
[0093] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0094] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, keeping the temperature for 4 hours, and finally cooling it naturally with the furnace;
[0095] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:10%Cr powder.
[0096] [Example 13]
[0097] Taking Al2O3:0.1%Cr at 1650℃ as an example, the specific operation steps are as follows:
[0098] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0099] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, keeping the temperature for 4 hours, and finally cooling it naturally with the furnace;
[0100] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:10%Cr powder.
[0101] [Example 14]
[0102] Taking Al2O3:0.01%Cr at 1650℃ as an example, the specific operation steps are as follows:
[0103] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired green stress-luminescent material;
[0104] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, keeping the temperature for 4 hours, and finally cooling it naturally with the furnace;
[0105] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:10%Cr powder.
[0106] [Example 15]
[0107] Taking Al2O3:0.5%Cr-2%Mn at 1650℃ as an example, the specific operation steps are as follows:
[0108] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, Mn is prepared using its chloride MnCl2 as the raw material, and the matrix is prepared using Al2O3 as the raw material. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is dried in an oven at 80°C to finally obtain the desired stress luminescent material;
[0109] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, keeping the temperature for 4 hours, and finally cooling it naturally with the furnace;
[0110] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr-2%Mn powder.
[0111] d) It has been detected that the addition of Mn can adjust the spectral intensity and spectral range to a certain extent.
[0112] [Example 16]
[0113] Taking Al2O3:0.5%Cr-2%Sb at 1650℃ as an example, the specific operation steps are as follows:
[0114] a) Raw materials: During the preparation, Cr uses its oxide Cr2O3 as the raw material, Sb uses its oxide Sb2O3 as the raw material, and the matrix uses Al2O3 as the raw material. First, weigh the raw materials of each element according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, put the raw materials into an agate bowl for grinding and mixing until they are evenly mixed. Subsequently, the mixed powder is placed in an oven at 80°C for drying to finally obtain the desired stress luminescent material;
[0115] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, keeping the temperature for 4 hours, and finally cooling it naturally with the furnace;
[0116] c) crushing and grinding the cooled powder obtained in step b), and passing it through a 150-mesh sieve to obtain near-infrared stress luminescent Al2O3:0.5%Cr-2%Sb powder.
[0117] d) It has been detected that the addition of Sb can adjust the spectral intensity and spectral range to a certain extent.
[0118] [Example 17]
[0119] Using Mn-Cr co-doping, taking Al2O3:0.5%Cr-1%LiF-1%KCl at 1650℃ as an example, the specific operation steps are as follows:
[0120] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, Al2O3 as the matrix, and LiF and KCl are added. First, weigh each element raw material according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is placed in an oven at 80°C for drying to finally obtain the desired stress luminescent material;
[0121] b) placing the uniformly ground powder in an alumina crucible, heating it to 1000°C at a heating rate of 10°C / min, then heating it from 1000°C to 1600°C at a heating rate of 5°C / min, then heating it from 1600°C to 1650°C at a heating rate of 2°C / min, keeping the temperature for 4 hours, and finally cooling it naturally with the furnace;
[0122] c) The powder is hard, and the cooled powder obtained in step b) is crushed with a powder crusher and then sieved. The obtained Mn-Cr co-doped powder can improve the near-infrared luminescence brightness.
[0123] [Example 18]
[0124] Using flux, taking Al2O3:0.5%Cr-120%NaCl at 1200℃ as an example, the specific operation steps are as follows:
[0125] a) Raw materials: During the preparation, Cr is prepared using its oxide Cr2O3 as the raw material, Al2O3 as the matrix, and NaCl is added. First, weigh the raw materials of each element according to the stoichiometric ratio, and then mix an appropriate amount of anhydrous ethanol or deionized water into the raw materials. Next, grind and mix the raw materials in an agate bowl until they are evenly mixed. Subsequently, the mixed powder is placed in an oven at 80°C for drying to finally obtain the desired stress luminescent material;
[0126] b) placing the evenly ground powder in an alumina crucible, heating it to 1200°C at a heating rate of 10°C / min, keeping it at that temperature for 2 hours, and finally cooling it naturally along with the furnace;
[0127] c) The obtained crystalline microcrystalline powder block was repeatedly washed with excessive deionized water to remove the NaCl molten salt, and then vacuum dried at 120° C. for 4 hours. The obtained Al2O3:0.5%Cr microcrystalline powder had dispersion characteristics.
Claims
1. A self-recovering near-infrared stress-luminescent alumina-based smart material, characterized in that: The chemical formula of the self-recovering near-infrared stress luminescent alumina-based smart material is Al2O3: m%Cr-n%Rz%D; 0.000001≤m≤10.9; 0<n≤2; 0≤z≤120; R is selected from one of Mn and Sb, D is added as a flux, and D is selected from one or more of Li, Na and K; m, n, z represent molar percentages; The preparation method of the self-recovering near-infrared stress luminescent alumina-based smart material comprises the following steps: Step 1, during the preparation, Al2O3 is prepared using its oxide, hydroxide or carbonate as a raw material, and Cr is prepared using its oxide, carbonate or soluble nitrate, sulfate, chloride as a raw material, and the addition amount is Al2O3: m% Cr-n% Rz% D, m%, 0.000001≤m≤10.9; Mn, Sb, use their oxides, or soluble nitrates, chlorides as raw materials, and the addition amount is n% of Al2O3: m%Cr-n%Rz%D, 0<n≤2; weigh the raw materials according to the stoichiometric ratio of each element in the chemical formula, and add a flux, the flux is one of LiF, NaF, KF, LiCl, NaCl, KCl, LiBr, NaBr or KBr, and the addition amount is z% of Al2O3: m%Cr-n%Rz%D, 0≤z≤120, m, n, z all represent molar percentages, add an appropriate amount of anhydrous ethanol or deionized water to the mixed raw materials, grind and mix evenly in an agate bowl, and then dry in an oven to obtain a mixed powder; Step 2: placing the ground powder in an alumina crucible, heating it to 1200-2050° C. in an air or oxygen atmosphere, burning it for 0.5-24 hours, and then cooling it naturally with the furnace; Step three, grinding the obtained cooled powder to obtain Al2O3: m%Cr-n%Rz%D powder with near-infrared stress luminescent material; drying in an oven at 80-300°C to obtain a mixed powder in the step one; heating to 1200-2050°C at a heating rate of 1-100°C / min in air or oxygen atmosphere in the step two, heating to near the melting point of alumina microcrystals.
2. Application of a self-recovering near-infrared stress-luminescent alumina-based smart material as a stress-luminescent material, characterized in that: The chemical formula of the self-recovering near-infrared stress luminescent alumina-based smart material is Al2O3: m%Cr-n%Rz%D; 0.000001≤m≤10.9; 0≤n≤2; 0≤z≤120; R is selected from one of Mn and Sb, D is added as a flux, and D is selected from one or more of Li, Na and K; m, n, z represent molar percentages; The preparation method of the self-recovering near-infrared stress luminescent alumina-based smart material comprises the following steps: Step 1, during the preparation, Al2O3 is prepared using its oxide, hydroxide or carbonate as a raw material, and Cr is prepared using its oxide, carbonate or soluble nitrate, sulfate, chloride as a raw material, and the addition amount is Al2O3: m% Cr-n% Rz% D, m%, 0.000001≤m≤10.9; Mn, Sb, use their oxides, or soluble nitrates, chlorides as raw materials, and the addition amount is n% of Al2O3: m%Cr-n%Rz%D, 0≤n≤2; weigh the raw materials according to the stoichiometric ratio of each element in the chemical formula, and add a flux, the flux is one of LiF, NaF, KF, LiCl, NaCl, KCl, LiBr, NaBr or KBr, and the addition amount is z% of Al2O3: m%Cr-n%Rz%D, 0≤z≤120, m, n, z all represent molar percentages, add an appropriate amount of anhydrous ethanol or deionized water to the mixed raw materials, grind and mix evenly in an agate bowl, and then dry in an oven to obtain a mixed powder; Step 2: placing the ground powder in an alumina crucible, heating it to 1200-2050° C. in an air or oxygen atmosphere, burning it for 0.5-24 hours, and then cooling it naturally with the furnace; Step three, grinding the obtained cooled powder to obtain Al2O3: m%Cr-n%Rz%D powder with near-infrared stress luminescent material; drying in an oven at 80-300°C to obtain a mixed powder in the step one; heating to 1200-2050°C at a heating rate of 1-100°C / min in air or oxygen atmosphere in the step two, heating to near the melting point of alumina microcrystals.
Citation Information
Patent Citations
Mechanoluminescent material and use applications thereof, raw material composition for mechanoluminescent material, and method for producing mechanoluminescent material
CN105209572A
Fluorescent powder capable of promoting plant growth and preparation method thereof
CN109874803A
Red light-emitting phosphors having co-activatior and manufacturing method thereof
KR100848002B1